Does renewable energy consumption add in economic growth? An application of auto-regressive distributed lag model in Pakistan - Nanthakumar, Loganathan; Muhammad, Shahbaz; Mohammad, Zeshan (Elsevier Science, 2015)
The objective of the study is to examine the relationship between renewable energy consumption and economic growth by incorporating capital and labour as potential determinants of production function in case of Pakistan. This study used auto-regressive distributed lag (ARDL) model and rolling window approach (RWA) for cointegration in context of Pakistan. The study used quarterly data over the period of 1972Q1–2011Q4. The causality analysis applied through VECM Granger causality and innovative accounting approaches. The results reveal that all the variables in the study are cointegrated that shows the long run relationship between the variables. Furthermore, renewable energy consumption, capital and labour boost economic growth. The causality analysis shows the feedback effect between economic growth and renewable energy consumption.